Pengaruh Citra Merek Terhadap Keputusan Orang Tua Siswa Memilih Jasa Pendidikan Di Madrasah Aliyah Negeri (MAN) Kubu Raya - Rusmini Rusmini; Dedi Hariyanto; Fita Kurniasari (Universitas Muhammadiyah Pontianak, 2018)
The objective of this research was to find out the influence of brand image on the decision of parents of students to choose education services at the Madrasah Aliyah Negeri (MAN) Kubu Raya. The research method used in this research was descriptive method. The analysis technique used is Simple Linear Regression analysis. The population in this research is the parents of active students in Madrasah Aliyah Negeri Kubu Raya in the 2017/2018 school year with a sample of 90 parents of students. The results of simple linear regression analysis showed the equation: Y = 1.395 + 0.679X. The results of the correlation coefficient test showed that the R value is 0.448 it can be concluded that the brand image has a strong relationship with the decision of parents of students to choose education services at the MAN Kubu Raya. The results of the coefficient of determination shows the value (R2) of 0.448 (44.8%), this value indicates that the influence of brand image on the decisions of parents of students choosing education services in MAN Kubu Raya is 44.8%, while the remaining 55.2% is influenced by other factors not examined in this research. The results of the model feasibility test showed that F value of 71.426>F table of 3.95, and has a significant value of 0.000 (less than 0.05), it can be concluded that a simple linear regression model can be used to predict the influence of brand image on parents decisions choose education services at MAN Kubu Raya.